Rethinking Foreign Culture and Social Studies: Students’ Perspective in A Southern Thailand Muslim School - Azkia Nur Shadrina Hayati; Ninuk Sholikhah Akhiroh (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to explore how Social Subjects shaped students’ perspectives and behaviors toward foreign cultures at the Muslim Santitham Foundation School in Southern Thailand. The research also identifies factors that challenge students in engaging with foreign cultures and explains the role of Social Subjects as a space for cross-cultural interaction. Data were collected using a qualitative approach through participatory observation and interviews over a one-month period. The results show that the students do not intentionally reject foreign cultures. Instead, their cautious behaviors are formed by long-term social habits through a homogeneous environment where the values of local culture are strongly rooted, limited interaction with foreign actors causes low confidence in using foreign languages, and less interactive teaching methods influence their ways of thinking and acting. However, the presence of foreign assistant teachers from Indonesia in Social Subjects created a new social arena that encouraged active participation, direct and meaningful interaction. It helped students to understand things that were previously seen as distant in their daily lives. This study highlights the importance of Social Subjects not only as a subject for theoretical knowledge, but also as a learning space for developing students’ social openness, while still maintaining their original cultural identity. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 10: Reduced Inequalities